2019
DOI: 10.17265/1548-6605/2019.02.003
|View full text |Cite
|
Sign up to set email alerts
|

The Political Law of Presidential Regulation on the Handling of Refugees in Indonesia

Abstract: Indonesia has been dealing with refugees since 1950s, despite the fact that the country has never been a party to the 1951 Refugees Convention and its 1967 Protocol. As of May 2017, according to UNHCR (United Nations High Commissioner for Refugees), Indonesia has been hosting 14,500 refugees from more than 57 countries. In handling of refugees, Indonesia puts forward the value of human rights that in line with its nation's ideology (Pancasila) and its constitutions (UUD 1945), and Regulation Number 39 Year 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…As a result, even though Indonesia is not a member to the 1967 Protocol Related to the Refugee Status and the 1951 United Nations Convention on the Status of Refugees, Indonesia has seen a substantial flow of refugees. However, the nation has demonstrated that it abides by the convention's spirit and fundamental tenets [16].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, even though Indonesia is not a member to the 1967 Protocol Related to the Refugee Status and the 1951 United Nations Convention on the Status of Refugees, Indonesia has seen a substantial flow of refugees. However, the nation has demonstrated that it abides by the convention's spirit and fundamental tenets [16].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas in terms of legal technicality, ratification would strengthen and enrich the national legal system so that it will better ensure the advancement and protection of human rights are better. Ratification could even become a shortcut to further bring closer the gap that exists between legal system at national and international level (Liza Shahnaz et al, 2019).…”
Section: Does Indonesia Have To Ratify the 1951 Convention?mentioning
confidence: 99%
“…Reg No. 125 of 2016) (Shahnaz et al, 2019;Afriansyah, 2018). This regulation regulates the handling of refugees starting from the discovery, security and supervision at the shelter.…”
Section: Introductionmentioning
confidence: 99%